Aktivitas Antihiperurisemia Mikroenkapsulasi Ekstrak Kulit Melinjo (Gnetum gnemon L.) secara In Vivo - Dhimas Adhityasmara; Yustisia Dian Advistasari; Bekti Nugraheni (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
Hyperuricemicis as an abnormally elevated uric acid level in the blood.Gnetumgnemon, locally known as Melinjo, is one of the Indonesian indigenous plantswhichcan be an alternative source of allopurinol. The peels of Gnetumgnemon, usually be wasted,contains red anthocyanin pigments possessing antioxidant activity owing toits potential for the inactivation of free radicals and peroxyls. However, the anthocyanin will chemically result incompound instability and is easily degraded during the period ofstorage. Encapsulation remains as one of the eminent formulation techniques usedto protect the active pharmaceutical compound through coating ofmainingredient with polymer forming smallersize of particles within micro tonano.This study was aimed at determining the Gnetumgnemonpeel extract in microencapsulated form in inducing antihyperuricemic activity. The male Wistar-strain rats wereused as subjects,groupedinto fivedifferent feeding treatments, i.e. negative group (carboxymethyl cellulose(CMC) Na 0.5%), positive group (allopurinol 12.6 mg/kg BM), andthree doses groups(i.e. 100 mg/kgBM, 200 mg/kg BM, dose group 300 mg/kg BM). Uric acid levels were initially assessed for each group, then every test-animals werefedwith a dose of 300mg/kg BM of potassium oxonate intraperitoneally,and 2.5 mL of chicken liver juiceorally. An hour interval was given for the uric acid levels measurement for each group. The results showed an increase in uric acid levels after the subjectswere treated accordingly with potassium oxonate 300mg/kg BM and 2.5 mL chicken liver juice. At the hour-2, there was a decrease in uric acid levels but showingno significant difference in everygroup (p 0.05). The significant decrease among the groups was found at hour-4and indicates that dose of 200mg/ kgBM is an effective dose in reducing uric acidlevelsKeyword: Gnetumgnemonpeel extract, microencapsulation, antihyperuricemic